The inhumanity of right - Giannaras, Chrēstos, 1935- (James Clarke & Co, 2021)
"Christos Yannaras' pioneering critique of the concept of the right of the individual is presented in English for the first time. This central aspect of political theory (since Hegel's Philosophy of Right) summarizes the philosophical and cultural identity of the paradigm of modernity, but the philosophical assumptions underlying the concept of right have not hitherto been subject to scrutiny. Yannaras shows that the starting-point of the concept of right is a phenomenalistic naturalism, which presupposes an abstract concept of the human subject as a fundamentally undifferentiated natural individual. The question is also explored of how the priority accorded to this concept of right is related to the contemporary crisis of the modern politico-social paradigm, while a new preface from the translator underlines the continued significance of Yannaras' proposal for Anglophone readers."--